Technologies for Heterogeneous Integration - Challenges and chances for fault isolation. (September 2017) - Boit, C.
Abstract: The evolution of electronic devices for Integrated Circuits following Moore's law is one of the fastest industrial development speeds – and still far too slow for the rapid increase of performance requirements demanded by Internet of Things, growing cloud computing and other innovations in microelectronics. 2D scaling following Moore's law may come to an end from now on. But, the explosion of data collection, exchange and storage will require a dramatic increase of operating frequency, requiring very low power, low latency, sensors & actuators. All these aspects will have consequences for contactless fault isolation (CFI) that go far beyond the challenges of the past, being mostly imaging resolution and operating frequency with a given basic material of silicon. The presentation will check the readiness of CFI for the scaling still in expectation by assessing optical probing using visible light. Heterogeneous Integration aspects like radio frequency operation, the influence of new materials for actives, optical interconnects, ultra-shallow TSV will be checked for risks and new opportunities of CFI. Together with test, reliability and security requirements, a new world of electronic devices is envisioned and options are presented how challenges to CFI may be mastered by taking chances for new concepts of debug and failure analysis. Highlights: Moore's law will not continue – optical probing with visible light will match resolution requirement Internet of Things (IoT) will require high data rate, increasing operating frequency drastically Photonic Interconnects and Built in Self Test for RF testability for Circuit Analysis New concepts for fault isolation in debug and failure analysis envisioned